Pemanfaatan Permainan Edukatif dalam Pembelajaran IPAS untuk Meningkatkan Motivasi Siswa Kelas 3 Sekolah Dasar (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Elementary school teaching in natural and social sciences (IPAS) often struggles to increase students' willingness to learn. Using educational games in the learning process is one strategy that can be used to overcome this problem. In addition to adding creativity and fun to the learning environment, educational games help students understand the concepts of IPS more deeply and more easily. This article discusses how educational games affect students' understanding of the material and how they can inspire learning in third graders. The results of this study indicate that the use of educational games can improve memory, increase student engagement, and help students connect theory to real-world applications. Therefore, using educational games to teach science is one innovative technique to improve the standard of teaching in elementary schools.